Disseminated aspergillosis following radiation therapy for medulloblastoma. Issue 714 (April 1985) - Hamilton, P.; Darbyshire, P. J.; McKeever, P.; Oakhill, A.
Abstract : A 16 year old girl who underwent surgery and radiotherapy for medulloblastoma is described. Shortly following the completion of treatment symptoms developed suggestive of tumour recurrence. At post mortem the cause was identified as disseminated aspergillosis with extensive cerebral involvement. The importance of this unusual complication is discussed.